Reconceptualizing the Nano-Enterprise: A Transaction Cost View of the Smallest Business Enterprise - Galang, Roberto Martin N (Archīum Ateneo, 2024)
This exploratory study characterizes the nano-enterprise -- or the single-person enterprise -- as a distinct category of firms that constitutes a significant pillar for economic activity and poverty alleviation in many parts of the world, especially in emerging markets. Because of their founders’ resource constraints, nano-enterprises focus less on increasing profitability and growing the business, but more on ensuring their own survival. Using the lens of transaction cost economics, this paper theorizes the genesis of nano-enterprises with a focus on the impact of institutional and technological change on firm survival. We apply a mixed-methods procedure leveraging on global survey data and a case study from the Philippines collected at the height of the Covid-19 pandemic to further theorize on the main characteristics that support nano-enterprise survival during times of crisis.